Minutes of Finance and General Purposes Committee (extract)
030-0108-001 MINUTE OF FINANCE AND GENERAL PURPOSES COMMITTEE, 25TH JULY, 1938. 158. INTERNATIONAL SOLIDARITY FUND - DISCUSSION WITH MINEWORKERS' FEDERATION. It was reported that a discussion had taken place between representatives of the Mineworkers' Federation of Great Britain, Mr. W. Schevenels, Joint Secretary of the International Solidarity Fund, and the General Secretary and Assistant Secretary of Congress on the question of a general scheme for the creation of a number of homes in France and/or Spain for orphans of Asturian miners to be maintained by means of the levy imposed by the Mineworkers' Federation. A very comprehensive report had been received from Mr. Schevenels on investigations he had made since the above meeting and it was reported to the Committee that a further meeting with representatives of the Mineworkers' Federation was to take place to discuss details. The report was NOTED. 292/946/30/108